Analisis Teknik dan Kesepadanan Penerjemahan Ungkapan Idiomatik dalam Cerpen The Cactus karya O. Henry - Putri Nur Amaliyah; Ika Sari Dewi (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines the translation strategies and the degree of meaning equivalence of idiomatic expressions in the short story The Cactus by O. Henry, analyzed based on idiomatic data in both the source text and the target text. The objectives of this study are to identify the types of idiomatic expressions, to analyze the translation strategies employed, and to evaluate the degree of meaning equivalence in the translated results. The method used is descriptive qualitative, employing content analysis techniques on 10 idiomatic expressions found in the source text and their Indonesian translations. The results show that there are three types of idioms, namely semi-idioms (60%), literal idioms (30%), and Pure idioms (10%), with semi-idioms being the most dominant type, indicating that the meanings of the expressions are relatively easy to understand within the context of the story. The translation strategies identified include modulation (40%), established equivalent (30%), adaptation (20%), and literal translation (10%), with modulation being the most dominant strategy. The degree of meaning equivalence reveals that dynamic equivalence (90%) is more dominant than formal equivalence (10%), indicating the translator’s tendency to prioritize naturalness and acceptability of meaning in the target language.